Investment Theory and Corporate Investment Decisions: A Theoretical and Empirical Review - Jalaluddin Rum; Muhamad Akbar; Miftahul Jannah; Muhammad Hisbullah (LP2M IAIN Palopo, 2026)
This study examines the role of investment theory in shaping corporate investment decisions amidst increasingly complex and dynamic economic conditions. The research focuses on how various investment theory approaches influence corporate investment decision-making and their impact on firm value and market efficiency. This study is conducted through a systematic literature review of classical and contemporary investment theories, including Modern Portfolio Theory, the Capital Asset Pricing Model, and behavioral finance approaches. Furthermore, this study examines empirical evidence and the implementation of these theories in corporate practice, particularly in aspects of capital budgeting, dividend policy, and investment behavior. A cross-sector case study analysis demonstrates that the contextual application of investment theory contributes to improved corporate performance. The research findings emphasize the importance of integrating theoretical frameworks and practical strategies by managers, investors, and policymakers to encourage corporate value creation and improve market efficiency, while also opening up opportunities for further research development.